Design and fabrication of finger rehabilitation device for stroke patients - a prototype development - Shahrol, Mohamaddan; Annisa, Jamali; Mohd Syahmi, Jamaludin (2014)
Fingers are important parts of human body. Major daily life activities are performed by using fingers. Stroke is an example of problem that can cause fingers malfunction. In order to have a chance for recovery, stroke patient need rehabilitation courses at the early stage of stroke. However, since the number of therapist is inadequate, there is a need to develop the homebased finger rehabilitation device to support the rehabilitation courses. In this project, the design and fabrication of the finger rehabilitation device is presented. The device was developed based on the wire-driven extension and flexion mechanism and controlled by a single on/off switch.